Kepekaan Erythricium salmonicolor Penyebab Penyakit Jamur Upas pada Kemiri Sunan terhadap Suhu, Cahaya, dan Fungisida - Florina, Dini; Wahyuno, Dono; Siswanto, Siswanto (Jurnal Fitopatologi Indonesia, 2017)
A typical pink disease symptom appeared on stem of Reutealis trisperma in Bogor. The present study was aimed for confirming the causal pathogen and testing its sensitivity to temperature, light and fungicides. The fungus was identified based on its morphological characteristics. The fungal inoculum was obtained by tissue isolation of infected stem bark. For pathogenicity test, the fungus was inoculated onto sterilized pieces of woody R. trisperma branch, then fastened on the seedlings and incubated in the green house. The effect of temperatures on fungal growth was tested by planting the fungal colony onto potato dextrose agar (PDA) then incubated at 25–34 °C. The sensitivity of the fungus to light was tested by inoculating the fungus into flask with potato dextrose broth (PDB) medium on a shaker (60 rpm) exposing it to white light tube (400 luks) or in a dark condition for 15 days at 25 °C. The obtained fungal colonies were weighed. Efficacy of copper hydroxide and mancozeb against the fungal colony growth was tested by inoculating the fungus onto PDA amended with 100, 200, 300, 400, and 500 ppm, respectively, of tested fungicides. The results showed that the causal pathogen was Erythricium salmonicolor. In the pathogenicity test, cobwebs of E. salmonicolor were formed on inoculated seedlings 3 weeks after inoculation. The optimum temperature for growth of E. salmonicolor was 28 °C. There was no significant effect of light on fungal growth. Mancozeb suppressed colony of E. salmonicolor growth better than copper hydroxide.